Analysis of THUG: a low-interaction client honeypot to identify malicious websites and malwares - Zulkurnain, Nurul Fariza; Rebitanim, Azli Fitri; Abdul Malik, Noreha (IEEE, 2018)
Cybersecurity is becoming more relevant throughout time. As information and technologies expand, so does the potential for it to be exploited. Computer and media have become more widespread in every modern country in the world. Unfortunately, certain community uses this opportunity to exploit the vulnerabilities that these computers left behind. Black hat, which is more identified as hackers and exploiters, uses the networks and servers that are commonly used to gain unauthorized information and data on the innocent victim. This work analyzes several honeypots and makes comparisons between them. Analysis has been done on the results to figure the disadvantages between each honeypot and try to improve one of the honeypots based on programming. The honeypot is deployed to simulate its effectiveness in combating cybercrime by detecting and collecting the information captured on the web browsers.